Céus Sobre as fronteiras: um estudo sobre astronomia Avá-Guarani, multiculturalidade e suas representações - Tavares, Aroldo da Silva (2015)
This dissertation presents itself as an interdisciplinary study mainly based on the methodology proposed by the micro history. With the central issue reminiscences of astronomy Avá-Guarani and its transmission, both in formal and in informal. The object of study was the Avá-Guarani-village Tekoa Ocoy and mostly students and state servers Indigenous Teko Ñemoingo College. However, the discussions extended by the tri-border region in particular the city of Foz do Iguaçu. We seek a real subjects of approach and also an analysis of speeches issued by them and about them. We also found some buildings and uses made by such representations, both by individuals and by institutions and large projects. Aim Avá-Guarani astronomy as the fundamental cultural feature to be preserved, and transmitted redefined, becomes an identity-forming element. We note, an indigenous culture in transformation, to get in touch with other forms of knowledge, especially the school, the non-indigenous she adapts. Astronomy showed us a real subjects and its dynamic culture, existing at the border, in the broadest sense, territorial, cultural, and economic, that redefining their existence and identity every day.